Constructing the Career Identity of Female Academicians: Mother Academician with Research Intention - Hatice Merve Bircan; Nihat Erdoğmuş (Journal of Economy Culture and Society)
The number of female academicians and research about them has increased in Turkey. Attention is drawn to the gap in the literature on how female academicians in Turkey construct their career (professional) identities. In this context, the purpose of this study is to research the process which female academicians follow in constructing their career identities. The study, which comes under the category of qualitativeresearch using phenomenological design, includes a total of 19 female academicians with the title of professor, associate professor, or assistant professor from the main academic fields of health sciences, technical sciences, administrative sciences, and social sciences. The interviews were conducted using semi-structured forms in accordance with a previously prepared protocol, and content analysis was applied to the data. The study obtained the findings that female academicians receive support from their families and spouse, define themselves as hard working, have specific role models for being an academician, work in their desired field, saw turning points in their lives at times of change in their doctoral period and marital status , and regard being published is an important criterion of success. As the basis of their career identities, the roles of their career stages have mainly been identified as “faculty member,” “mother,” and “researcher.” Having multiple roles was seen to cause problems with balancing roles.